In vitro analysis of total and ionizable fluoride in different toothpaste formulation - Deveza, Ronald M.
Fluoride is added into toothpaste for its anti-caries activity. The World Health Organization (WHO) recommends 1200 ppm to 1500 ppm of ionizable fluoride in toothpaste while the Philippine Food and Drug Administration (FDA) limits to a maximum of 1500 ppm of total fluoride. The study aimed to determine the effects of different types of toothpaste formulation in the results of tests for total and ionizable (soluble and ionic) Fluoride using the Bardal Method. Preliminary screening of the effects of 10% variation in concentrations of abrasives on Fluoride was performed to determine the optimum amount of abrasive. No significant difference was observed in the results of preliminary screening of the abrasives (Calcium Carbonate, Aluminum Oxide Trihydrate, Dicalcium Phosphate and Silicon Dioxide) on the active ingredients (Sodium Fluoride and Sodium Monofluorophosphate). Eight toothpaste formulations were prepared containing four different abrasives and two different sources of Fluoride. Fluoride analyses were performed using the Bardal Method for total, soluble and ionic Fluoride. A six-month stability study was conducted on the eight formulations resulted in stable organoleptic properties and Fluoride content. No significant difference was observed in the total Fluoride and soluble Fluoride of the toothpaste formulations with Sodium Monofluorophosphate. There was no significant difference in the total Fluoride among the formulations but there was a significant difference between the soluble Fluoride and ionic Fluoride. The total Fluoride, soluble fluoride and ionic Fluoride of toothpaste with Sodium Fluoride as active and Silicon Dioxide as abrasive had no significant difference (p-value = 0.706, α = 0.05). The Fluoride results of the eight toothpaste formulations were comparable to the Fluoride results during the preliminary screening.